2017
DOI: 10.1111/aji.12676
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Wnt10b and activation of β‐catenin/GCMa/syncytin‐1 pathway in BeWo cell fusion

Abstract: Wnt10b is involved in forskolin/hCG-mediated BeWo cell fusion via β-catenin/GCMa/syncytin pathway, which may also involve activation of PKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Also, it has been reported that a feedback loop involving Gcm1 and Frizzled regulates trophoblast differentiation and chorionic branching morphogenesis 8 . Additionally, Wnt10b is involved in the activation of β-catenin/GCM1 pathway during the process of BeWo cell fusion after forskolin/hCG treatment 9 . These findings suggested that Gcm1 may be linked with Wnt signaling pathway, which can affect its activity to control cell fate.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been reported that a feedback loop involving Gcm1 and Frizzled regulates trophoblast differentiation and chorionic branching morphogenesis 8 . Additionally, Wnt10b is involved in the activation of β-catenin/GCM1 pathway during the process of BeWo cell fusion after forskolin/hCG treatment 9 . These findings suggested that Gcm1 may be linked with Wnt signaling pathway, which can affect its activity to control cell fate.…”
Section: Introductionmentioning
confidence: 99%
“…Success of pregnancy relies on the differentiation, proliferation, and invasion of placental trophoblast cells during early pregnancy [26,27] . The dysfunction of trophoblast may lead to severe complications threatening both the mother and the developing fetus and resulting in economic losses.…”
Section: Discussionmentioning
confidence: 99%
“…BeWo cells (0.1 × 10 6 /well), seeded 24 h prior in 6‐well cell culture plates, were transfected with optimized concentration of either miR‐27b‐5p mimic (50 nM) & mimic control (50 nM; GE Dharmacon™), or WNT2B siRNA, HSD3β1 siRNA & control siRNA (40 pmol; Qiagen) using lipofectamine™ RNAiMAX transfection reagent (LifeTechnologies) and Opti‐MEM ® (Gibco®) essentially as described previously 18 . In addition, BeWo cells were also co‐transfected with miR‐27b‐5p mimic and optimized concentration of either mammalian HSD3β1 (300 ng/ml; Sino Biological) or WNT2B (500 ng/ml; Sino Biological) expression vector to see, if overexpression of HSD3β1/WNT2B can rescue the effect of miR‐27b‐5p mimic on forskolin‐mediated BeWo cell fusion.…”
Section: Methodsmentioning
confidence: 99%
“…Qiagen) using lipofectamine™ RNAiMAX transfection reagent (LifeTechnologies) and Opti-MEM ® (Gibco®) essentially as described previously. 18 In addition, BeWo cells were also co-transfected with miR-27b-5p mimic and optimized concentration of either mammalian HSD3β1 (300 ng/ml; Sino Biological) or WNT2B (500 ng/ml; Sino Biological) expression vector to see, if overexpression of HSD3β1/ WNT2B can rescue the effect of miR-27b-5p mimic on forskolinmediated BeWo cell fusion. After 48 h of transfection, cells were processed for cell viability, fusion, qRT-PCR, and Western blotting.…”
Section: Bioinformatics Analysis Of Mir-27b-5p Targetsmentioning
confidence: 99%